Listening To Teachers’ Voices: Constructs On Music Performance Anxiety In Artistic Education - Moura, Nádia (2021)
Music performance anxiety is an acknowledged condition amongst musicians from early learning stages to professional levels. Anxiety experienced in uncontrolled levels translates into the development of physiological and psychological symptoms that impair performance skills and may, ultimately, lead to post-traumatic stress disorders and drop-out of music-related activities. This paper focuses on teacher’s voices to justify the need for inclusion of anxiety management training in music schools’ curricula as means of promoting well-being, coping with stress-inducing situations, and boosting growing musicians’ performative experiences through positive pedagogies. Semi-structured interviews were conducted to four instrument teachers of a Portuguese institution of specialized artistic education to collect data about previous experiences, conceptions, and ways of teaching MPA managing. The importance of integrating coping strategies in pedagogical practices, its obstacles and benefits, alongside suggestions for conceiving viable intervention projects in schools were discussed by the interviewed and hereby critically presented with respect to existing literature.